The 2019 Winter Universiade in Krasnoyarsk. The student campus - Krylova, Irina (project baikal, 2017)
The uniqueness of the 29th World Winter Universiade in Krasnoyarsk is that all the sports grounds will be located within the city. One of them is the territory of the Siberian Federal University, which will house the Athletic Village and the volunteers’ residence. The facilities that are being built on this territory will later frm a student environment. A common natural framework between the facilities and the city is created with the help of a continuous chain of parks and gardens. The student boulevard will link two grounds, while running through the birchwood along the paths already made by people. The project approach implies searching for a code of the Krasnoyarsk architecture. According to the reconstruction project, the age-old pines will be preserved, new pines will be planted, and the view to the mountains will be open.
Keywords: natural framework; Universiade Village; Studgorodok; the right bank; pine